Embodiment as a Means of Communication in Establishing a Reputation: A Literary Analysis of Wisdom from Proverbs 12:23 - Handayani, Magpika; Bae, Sung Hyun; Sualang, Farel Yosua (Sekolah Tinggi Teologi Transformasi Indonesia, 2024)
Abstract: Research on reputation building indicates that an individual's reputation relies on the combination of integrity with their social surroundings, viewing reputation through the lens of social interactions of that person. Additionally, reputation formation is observed in how an individual prioritizes integrity, even when faced with challenging social conditions; reputation is shaped by the social visibility of one's past actions. Nonetheless, this study highlights that reputation goes beyond mere verbal communication and social engagement—it undeniably incorporates the physical aspect. This article explores the idea of building a reputation through embodiment, illustrating the significant role the body plays in shaping a person’s reputation, examined through Proverbs 12:23. The research employs a literary analysis framework focused on the wisdom derived from Proverbs 12:23, utilizing figurative interpretation as a means of analysis. Various types accompany the interpretation in extracting the gist of Proverbs 12:23—related to embodiment for repute in non-verbal communication. Findings reveal that embodiment significantly influences one's societal reputation, integrity, and past conduct. The terms “cover” and “proclaim” suggest verbal expression and can be deduced from physical gestures. Therefore, verbal communication is seen as enhanced and substantiated by embodiment, significantly governing an individual's reputation.